Full access to nanoscale bismuth - Palladium intermetallics by low-temperature syntheses - Heise, Martin; Chang, Jen-Hui; Schoenemann, Rico; Herrmannsdoerfer, Thomas; Wosnitza, Joachim; Ruck, Michael (Chemistry of Materials, 2014)
The microwave-assisted polyol process was applied and modified to synthesize phase-pure micro- or nanocrystalline samples of all intermetallic phases in the bismuth - palladium system. Reaction temperatures range between 170 and 240 °C, whereas conventional syntheses from melt necessitate 500 to 1000 °C. Reaction times of few minutes up to 1 h are sufficient. Although not stable at the temperature of synthesis, high-temperature phases are accessible as well. Differences in the redox potentials of the two metals have effectively been compensated by adding auxiliaries such as oleylamine, oleic acid, and potassium hydroxide. The samples were characterized by X-ray powder diffraction, scanning electron microscopy, and energy-dispersive electron spectroscopy. Magnetic properties and electrical conductivity of the nanocrystalline samples were measured. The high temperature compound γ-BiPd showed superconductivity with Tc = 3.2 K. Nanocrystalline nc-Bi2Pd5 revealed an unusual temperature dependence of the electrical conductivity indicating an electronic phase transition at about 230 K. The electronic band structures of γ-BiPd, Bi2Pd5, Bi12Pd31, and BiPd3 were calculated including spin - orbit coupling. (Graph Presented).
CRIS-Team Scopus Importer:2023-03-20